microRNAs in Autism Spectrum Disorders - Vasu, Mahesh M.; Sumitha, Puthiripadath S.; Rahna, Parakkal; Thanseem, Ismail; Anitha, Ayyappan (Current Pharmaceutical Design, 2019)
Background: Efforts to unravel the extensive impact of the non-coding elements of the human genome on cell homeostasis and pathological processes have gained momentum over the last couple of decades. miRNAs refer to short, often 18-25 nucleotides long, non-coding RNA molecules which can regulate gene expression. Each miRNA can regulate several mRNAs. Methods: This article reviews the literature on the roles of miRNAs in autism. Results: Considering the fact that 1% of the human DNA encodes different families of miRNAs, their overall impact as critical regulators of gene expression in the mammalian brain should be immense. Though the autism spectrum disorders (ASDs) are predominantly genetic in nature and several candidate genes are already identified, the highly heterogeneous and multifactorial nature of the disorder makes it difficult to identify common genetic risk factors. Several studies have suggested that the environmental factors may interact with the genetic factors to increase the risk. miRNAs could possibly be one of those factors which explain this link between genetics and the environment. Conclusion: In the present review, we have summarized our current knowledge on miRNAs and their complex roles in ASD, and also on their therapeutic applications.
Keywords: Autism spectrum disorders